Unital positive Schur multipliers on S_n^p with a completely isometric dilation - Duquet, Charles (Mathematica Scandinavica, 2024)
Let 1<p eq 2<∞ and let S^p_n be the associated Schatten von Neumann class over n× n matrices. We prove new characterizations of unital positive Schur multipliers S^p_n→ S^p_n which can be dilated into an invertible complete isometry acting on a non-commutative L^p-space. Then we investigate the infinite dimensional case.